Quality Characteristics Of Duck Surimi-Like Material Using Acid And Alkaline Solubilization Methods - Tina, Nurkhoeriyati (2012)
The scarcity of surimi raw material has brought about the development of new raw material from species other than fish, which is known as surimi-like materials (SLM). Spent duck is one of the potential raw materials for SLM. Researchers have developed the technology to obtain functional protein isolates from dark muscle by solubilizing the muscle proteins in either acid or alkaline conditions. The objective of this project was to explore the quality characteristic of duck SLM. Acid solubilization recovered duck protein (ACS) and alkaline solubilization recovered duck protein (ALS) had significantly higher protein and lower fat contents (P < 0.05) than untreated duck meat and conventionally recovered duck protein (CON). The ACS process yielded the highest (P < 0.05) protein recovery. The ALS process generated the highest lipid reduction (P < 0.05). CON had the highest (P < 0.05) gel strength, salt extractable protein (SEP), water holding capacity (WHC), Ca2+-ATPase activity and most texture profile analysis (TPA) attributes. ACS and ALS gels had significantly higher (P < 0.05) whiteness values than untreated duck meat and CON gels. ACS and CON had significantly higher (P < 0.05) myoglobin removal than ALS and untreated duck meat. Untreated had the highest total Sulfhydryl (SH) group content. ACS and ALS had significantly higher (P < 0.05) indispensable amino acids (IAA) content among all samples. Sodium Dodecyl Sulfate - Polyacrylamide Gel Electrophoresis (SDS-PAGE) analysis showed that CON had the largest content of myosin heavy chain (MHC). Saturated fatty acid (SFA) composition of CON were significantly higher (P < 0.05) than that of ACS or ALS. This result is in contrast with poly unsaturated fatty acids (PUFA) composition. ACS had significantly higher (P < 0.05) content of Fe, Na, Ca and Mg than that of ALS.